Separation of Sm-Eu-Gd mixed solutions using bifunctional ionic liquid [A336][P204] - Ismail, N. A.; Hisyam, A.; Shariff, S. (AIP Publishing, 2019)
This paper studied the use of bifunctional ionic liquid as an extractant to extract and separate Sm-Eu-Gd mixed solutions. The extractant combined the conventional extractant di-(2-ethyl hexyl) phosphate (P204) with ionic liquid Aliquat 336 (A336) through acid/base neutralization method. This work explored the effect of extraction medium (chloride, sulphate and nitrate), acid concentration (1.5-5.0 M) and organic to aqueous phase ratio (1:1, 3:2, 7:3, 4:1, 9:1) to determine the separation factor of each metals. Based on the results, Sm(III) showed the highest separation factor of total solute (βSm/total-Sm=2.81) in the nitrate medium with the acid concentration of 3.0M and organic to aqueous phase ratio of 4:1. Sm(III) was chosen to be separated in the first stage of extraction from the Sm-Eu-Gd mixed solution. In the second stage, the optimized condition to separate the remaining Eu-Gd mixed solution into individual metal was also in the nitrate medium with organic to aqueous phase ratio of 3:2, except with lower acid concentration, 2.0M. This work shows that [A336][P204] is an impeccable extractant candidate for an improved and environmental friendly to separate Sm-Eu-Gd in both laboratory and industrial application.